2004
DOI: 10.1161/01.hyp.0000129540.83284.ca
|View full text |Cite
|
Sign up to set email alerts
|

Complement 3 Is Involved in the Synthetic Phenotype and Exaggerated Growth of Vascular Smooth Muscle Cells From Spontaneously Hypertensive Rats

Abstract: Abstract-Vascular smooth muscle cells (VSMCs) from spontaneously hypertensive rats (SHR) show the synthetic phenotype and exaggerated growth in comparison with VSMCs from normotensive Wistar-Kyoto (WKY) rats. We investigated genes associated with the synthetic phenotype and exaggerated growth of VSMCs from SHR by microarray. Expression of 1300 transcripts was evaluated by microarray with total mRNA extracted from mid-layer aortic smooth muscle of 3-week-old SHR/Izumo and WKY/Izumo rats. mRNAs encoding sodium-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 29 publications
4
50
0
Order By: Relevance
“…Recently, we demonstrated by microarray analysis that C3 mRNA is produced in smooth muscle from SHR in vivo but is not expressed in smooth muscle from Wistar Kyoto rats. In contrast, there were no differences in levels of mRNAs for C4, C8, and C9 in aortic smooth muscle cells from SHR and Wistar Kyoto rats (Lin et al, 2004). These data suggest that expression of C3 in VSMCs is independent of that of other complement system components and that C3 has unique effects on VSMCs.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Recently, we demonstrated by microarray analysis that C3 mRNA is produced in smooth muscle from SHR in vivo but is not expressed in smooth muscle from Wistar Kyoto rats. In contrast, there were no differences in levels of mRNAs for C4, C8, and C9 in aortic smooth muscle cells from SHR and Wistar Kyoto rats (Lin et al, 2004). These data suggest that expression of C3 in VSMCs is independent of that of other complement system components and that C3 has unique effects on VSMCs.…”
Section: Discussionmentioning
confidence: 65%
“…We found that complement 3 (C3) is expressed in spontaneously hypertensive rat (SHR)-derived VSMCs that show the synthetic phenotype and exaggerated growth. We found that C3 causes VSMCs to convert from the contractile to the synthetic phenotype to stimulate growth (Lin et al, 2004).…”
mentioning
confidence: 78%
“…A study of spontaneously hypertensive rats showed that C3 stimulated the exaggerated growth of vascular smooth muscle cells, independently of other complement factors. 23 Acylation stimulating protein (ASP) is produced by cleavage of C3. 31 ASP is a metabolically active molecule and has been associated with increased glucose uptake and fatty acid storage in the adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
“…22 A recent study of spontaneously hypertensive rats reported that C3 was produced by arterial smooth muscle cells, and importantly, that C3 stimulated the exaggerated growth of these cells. 23 However, to the best of our knowledge, no study has explored whether C3 or C4 predict the development of hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…The article by Lin et al in this issue 3 describes an important finding of a differential expression of the complement protein C3 in the exaggerated growth of arterial smooth muscle cells from SHRs of an age (3 weeks) that precedes measurable increases in blood pressure. The authors first study medial tissues from whole arteries and, using gene chip analyses, demonstrate that several genes are expressed in SHR tissues but not Wistar-Kyoto rat (WKY) tissues; other genes are expressed in both but at either lower or higher levels in SHRs versus WKYs.…”
Section: Complementmentioning
confidence: 99%